Maximizing Bali Village Tourism Potential Using Penta-Helix Model - Novianti, Khusnul Rofida (Universitas Pendidikan Ganesha, 2021)
The rapid growth of the tourism sector has made the government committed to implementing the principle of sustainable tourism development. To develop regional tourism, it is relatively necessary to direct, integrated, cross-sectoral, and sustainable programs so that the economic benefits of tourism are increasingly felt evenly distributed by the community. Bali, popular as one of the most tourist destinations in the world, is used as an example for the development of a national destination by the Indonesian government by creating 10 new Bali destinations, but this scheme must be postponed due to the covid-19 outbreak that hit Indonesia. This study aims to explore the sustainable tourism strategy in Bali’s village tourism sector using a qualitative approach based on content analysis based on secondary data since Bali has the largest number of village tourism in Indonesia using the Penta-helix model (synergy between academic, business, community, government, and media). With the synergy and collaboration of these five central sectors (especially during decreasing tourism sector of coronavirus outbreak), it is expected to increase awareness and maximizing the potential among the public regarding Bali sustainable tourism.